2018
DOI: 10.1002/ejsp.2553
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived warmth and competence on realistic threat and willingness for intergroup contact

Abstract: Unwillingness for contact with outgroup members is a form of prejudice. In two studies, we tested the proposition that perceived competence has an indirect effect on willingness for intergroup contact through its effect on realistic threat, and that perceived warmth moderates this relationship. In Study 1, Hong Kong students (N = 144) rated the perceived warmth and competence of an outgroup, Mainland Chinese students, as well as the extent to which they perceived the group as presenting a realistic threat, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Warmth refers to the degree of foods made by robotic chef with sincerity, love and passion. Items for warmth were adapted from Fiske et al (2002), Awale et al (2019) and Fuchs et al (2015). This portion contained four items.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Warmth refers to the degree of foods made by robotic chef with sincerity, love and passion. Items for warmth were adapted from Fiske et al (2002), Awale et al (2019) and Fuchs et al (2015). This portion contained four items.…”
Section: Measurementmentioning
confidence: 99%
“…Competence refers to the ability of robotic chef to make high quality foods. Items for competence were adapted from Fiske et al (2002) and Awale et al (2019). This portion contained five items.…”
Section: Robot With Humanoid Handsmentioning
confidence: 99%
“…Nonetheless, a number of studies employing the SCM and the BIAS map have used a different response instruction, focusing on participants’ evaluations from their own individual perspective . Diverging from the original social, group-centered, shared cultural perspective, these studies instructed their participants to express personal stereotypical beliefs, by for instance asking them about “your opinion about a particular group” or “how (e.g., warm) do you think this person is” ( Becker and Asbrock, 2012 ; Koschate et al, 2012 ; Matthews and Levin, 2012 ; Durante et al, 2014 ; Awale et al, 2018 ; Constantin and Cuadrado, 2019 ; Kotzur et al, 2019b , Study 2; Sweetman et al, 2013 ; Ponsi et al, 2016 ; Sink et al, 2018 , Study 2; Ufkes et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leaders arguably will see competent but cold followers as threats because these followers have the ability to carry out their bad intentions to challenge the leader's position. Indeed, previous studies have shown that people are more likely to see out‐group individuals as threats when they perceive them as being competent and cold (Awale, Chan, & Ho, 2019). More directly relevant to our research, Tai et al (2012) suggested that employees with high competence and low warmth are more likely to trigger leaders' envy toward employees.…”
Section: Threat‐based Tripartite Model Of Procedural Justice Enactment: Position Stability Follower Competence and Follower Warmthmentioning
confidence: 99%